Residues Leu261, Trp264, and Phe265 Account for Apolipoprotein E-Induced Dyslipidemia and Affect the Formation of Apolipoprotein E-Containing High-Density Lipoprotein - Drosatos, Konstantinos (2007)
Overexpression of apolipoprotein E (apoE) induces hypertriglyceridemia in apoE-deficient mice, which is abrogated by deletion of the carboxy-terminal segment of residues 260–299. We have used adenovirus-mediated gene transfer in apoE(−/−) and apoA-I(−/−) mice to test the effect of three sets of apoE mutations within the region of residues 261–265 on the induction of hypertriglyceridemia, the esterification of cholesterol of very low-density lipoprotein (VLDL) and high-density lipoprotein (HDL), and the formation of spherical or discoidal apoE-containing HDL. A single-amino acid substitution (apoE4-[Phe265Ala]) induced hypertriglyceridemia in apoE(−/−) or apoA-I(−/−) mice, promoted the accumulation of free cholesterol in the very low-density lipoprotein (VLDL) and HDL region, and decreased HDL cholesterol levels. A double substitution (apoE4[Leu261Ala/Trp264Ala]) induced milder hypertriglyceridemia and increased HDL cholesterol levels. A triple substitution (apoE4-[Leu261Ala/Trp264Ala/Phe265Ala] or apoE2-[Leu261Ala/Trp264Ala/Phe265Ala]) did not induce hypertriglyceridemia and increased greatly the HDL cholesterol levels. Electron microscopy (EM) analysis of the HDL fractions showed that apoE4-[Leu261Ala/ Trp264Ala/Phe265Ala] and apoE2-[Leu261Ala/Trp264Ala/Phe265Ala] contained spherical HDL, apoE4-[Leu261Ala/Trp264Ala] contained mostly spherical and few discoidal HDL particles, and apoE4-[Phe265Ala] contained discoidal HDL. We conclude that residues Leu261, Trp264, and Phe265 play an important role in apoE-induced hypertriglyceridemia, the accumulation of free cholesterol in VLDL and HDL, and the formation of discoidal HDL. Substitution of these residues with Ala improves the apoE functions by preventing hypertriglyceridemia and promoting formation of spherical apoE-containing HDL.